An Analysis of Educational Values in Surah An-Nisa: A Thematic Approach Through the Lens of Tafsir Ibn Kathir - Sumarno, Sumarno; Fitriyah, Alfina Wildatul; Izza, Rifda (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2025)
This study investigates the educational values embedded in Surah An-Nisa using a thematic approach (maudhū‘ī) and refers primarily to Tafsir Ibn Kathir as a classical exegetical source. The background of this research lies in the urgent need to reintegrate Qur’anic values into the contemporary education system, particularly in light of growing moral crises and the erosion of ethical standards among students. The study aims to explore how Surah An-Nisa, as a chapter rich in legal and social injunctions, contributes to the Islamic educational framework through the lens of classical interpretation. This research employs a qualitative method with a library research approach, where data is collected from primary sources such as the Qur’an and Tafsir Ibn Kathir, alongside secondary sources including books, scholarly articles, and other relevant references on Islamic education. The analysis is conducted thematically by identifying verses that contain educational implications and interpreting them based on the exegetical insights of Ibn Kathir. The findings reveal that Surah An-Nisa offers a wide range of educational values such as justice, gender equity, family integrity, social responsibility, protection of vulnerable groups, and obedience to divine law. These values, as elaborated in Tafsir Ibn Kathir, serve not only as religious commandments but also as moral and social principles that can shape individual behavior and communal harmony. The study concludes that these values are highly relevant for contemporary educational practices and should be integrated into modern Islamic curricula to nurture holistic and ethical learners.